Health Promotion Edugame Media "Healthy Snacks" for Elementary School Students - Susilowati, Prima Endang; Listyawardhani, Yana; Nurhamzah, Lutfi Yulmiftiyanto; Husnul, Nisatami; Abdurrahmat, Asep Suryana (Jurnal Abmas Negeri (JAGRI), 2025)
The nutritional needs of school-age children increase with physical activity and rapid growth, yet many children do not consume a balanced, nutritious diet. One reason is the habit of consuming unhealthy snacks, which are generally low in nutrients and high in sugar, salt, and fat. This activity aims to increase elementary school students' knowledge about healthy and nutritious snacks through interactive, game-based education (edugame). The activity design included providing education to students and teachers, accompanied by pre-tests and post-tests to measure the level of knowledge. Initial observations showed that the types of snacks sold around the school consisted of wet snacks, dry snacks, and packaged drinks with varying nutritional qualities. After education through edugame media, there was an increase in student knowledge as indicated by an increase in the average score from 65,0 (sufficient category) to 73,2 (good category), with a difference of 8,2 points. Based on the classification of knowledge levels, before education, 25% of students were in the good category, 46,3% were sufficient, and 28,7% were poor. After the activity, the proportion of students in the good category increased to 47,5%, while the fair category decreased to 40% and the poor category to 12,5%. These results indicate that the edugame method is effective in improving students' understanding of the concept of healthy snacks. It is recommended that schools integrate this educational activity into thematic learning or extracurricular activities, and collaborate with relevant agencies such as community health centers or health departments to support the program's sustainability.